Nesplora Ice Cream test: a normative study of a virtual reality-based executive function assessment in adults - Fidel Rebón-Ortiz; Fidel Rebón-Ortiz; Débora Areces; Miguel Saura-Carrasco; Claudia Flores; Celestino Rodríguez; Unai Díaz-Orueta; Unai Díaz-Orueta; Gema Climent; Irene Alice Chicchi Giglioli (Frontiers in Psychology)
This study aims to establish normative data for participants aged 17 to 80 who completed the Nesplora Ice Cream test, a virtual reality tool designed to assess executive functions. The objective is to provide a comprehensive reference for evaluating executive function performance in healthy adults across different age groups. A total of 419 participants (51% female) were recruited from nine locations in Spain. Trained evaluators administered the Nesplora Ice Cream test. The study utilized empirical analysis to identify key factors related to executive function, focusing on planning, learning, and flexibility. Cluster analysis was employed to define age groups for each factor: 17–40, 41–61, and 62–80 for planning; 17–44, 45–61, and 62–80 for learning; and 17–20, 21–36, and 37–80 for flexibility. The analysis revealed three main factors—planning, learning, and flexibility—that characterize executive function performance. No significant gender differences were found. Descriptive normative data were provided based on age and gender. Confirmatory factor analysis supported the three-factor structure of the test. Additionally, data on the validity, reliability, and internal consistency of the test were included. These normative data are valuable for assessing executive functions in an ecologically valid way. The findings provide a robust reference point for studying the early identification of executive dysfunction in adults and the impact of neurodegenerative conditions in clinical settings. Further research is needed to evaluate the test’s sensitivity and specificity in clinical populations. These norms enable the development of timely, personalized interventions for individuals showing executive function impairments.